Anion sensitivity and spectral tuning of cone visual pigments in situ. - Kleinschmidt, J (1992)
We tested the effect of anions on the absorbance spectrum of native visual pigments as measured by microspectrophotometry in individual cone outer segments of four species of fish and one species of amphibian. In all species tested, the long-wavelength-absorbing cone pigments were anion sensitive, and their lambda max could be tuned over a range of 55 nm depending on the identity of the anion present. Cl- and Br- were the only anions that produced native pigment spectra by red shifting lambda max from its value under anion-free conditions. Lyotropic anions such as NO3-, SCN-, BF4-, and ClO4- caused substantial and graded blue shifts of lambda max. The apparent Kd of binding sites on the pigment for Cl- and for ClO4- was approximately 2 mM. Taken together with previous findings on three visual pigments from the reptilian, avian, and amphibian classes, our results support the hypothesis that all long-wavelength-absorbing vertebrate visual pigments are spectrally tuned in part through the binding of a chloride ion. We propose that the site of anion tuning is near the protonated Schiff base of the chromophore, whose counterion may be complex and include Cl- as an exchangeable anion. This counterion configuration may resemble the one present in the light-driven Cl- pump halorhodopsin.